Thoughts about Suicide and Self-Harm in Patients with Tinnitus and Hyperacusis - Aazh, Hashir; Moore, Brian C. J. (Journal of the American Academy of Audiology, 2018)
There are conflicting reports with regard to the relationship between suicidal ideations and tinnitus and hyperacusis. Audiology departments play a major role in offering therapy and support for patients experiencing tinnitus and hyperacusis. If suicidal and self-harm ideations among patients seen in audiology clinics are high, then it would be important to screen for them to make onward referrals to mental health services.The aim of this study was to assess the prevalence of and factors related to suicidal and self-harm ideations in patients with tinnitus and hyperacusis seen at an audiology outpatient service.This study was a part of a service evaluation survey using a correlational design. All patients who sought help concerning their tinnitus or hyperacusis from an audiology clinic of the National Health Service in the United Kingdom in a 1-yr period were asked to complete the survey questionnaires (n = 402).The focus of this article is on analysis of the patients’ responses about suicidal and self-harm ideations as measured via the Patient Health Questionnaire, item 9, and their associated factors.A total of 150/402 of patients answered the question about suicidal and self-harm ideations. Of these, 13% indicated that they had suicidal or self-harm ideations in the past 2 weeks. Suicidal and self-harm ideations were moderately correlated with scores on the anxiety and depression subscales of the hospital anxiety and depression scale. Suicidal and self-harm ideations decreased with increasing age. There were small statistically significant correlations between suicidal and self-harm ideations and tinnitus handicap, hyperacusis handicap, insomnia, and scores on the visual analog scale (VAS) of effect of tinnitus on life. The correlations between suicidal and self-harm ideations and gender, pure-tone average of the worse and better ears, uncomfortable loudness levels of the worse ears, and VAS of tinnitus loudness and annoyance were not statistically significant. A regression model showed that abnormal depression scores increased the chance of suicidal and self-harm ideations by a factor of 6.2 (95% confidence interval = 1.13–34.1, p = 0.036).Audiologists offering tinnitus and hyperacusis rehabilitation should screen for suicidal and self-harm ideations among patients, especially for those with comorbid depression, and make onward referral to appropriate services when needed.
Keywords: hyperacusis; self-harm; suicide; tinnitus